Influence Culture on Perceptions, Behaviors, and Risk of Repeat Attacks Patients with Heart Disease: A Literature Review Based on Transcultural Nursing - Trisna, Made Oktaviani Bulan; Suyasa, I Gede Putu Darma; Israfil; Suantika, Putu Inge Ruth (Babali Nursing Research, 2025)
Introduction: Differences in values, norms, and customs across societies shape how patients understand their illness, make decisions about seeking care, and undergo treatment and recovery. Based on a transcultural nursing approach, this study aims to synthesize findings from various literatures that identify cultural influences on heart disease management and their implications for preventing recurrent heart attacks. Methods: This study was a narrative literature review with the PICO framework, using PubMed, ScienceDirect, Google Scholar, and relevant sources (2016–2025) with the keywords “Coronary heart disease” AND “transcultural nursing” AND “culture.” Inclusion criteria included qualitative and quantitative primary research on the role of “culture” OR, “ethnicity” OR, “spirituality” OR, “gender” OR,  OR “access to healthcare in heart disease.” Did not address the transcultural context, focused only on biological factors, review/meta-analysis, single case report, and inadequate methodology were excluded. Of the 1,539 articles identified, 15 met the criteria and were analyzed narratively. Results: The study identified six aspects of the role of culture in heart disease: disease perception (local beliefs and spirituality), coping and treatment seeking (family norms, traditional practices, access), ethnic and gender inequalities, immigrant acculturation (Western lifestyle), collectivism and family roles (compliance vs. delay of help), and local environmental factors/traditions (e.g., solid fuels). Culture can be both a risk and a protective factor through family support, spirituality, and community. Conclusion: Culture is important in preventing and managing heart disease, particularly in reducing the risk of recurrent heart attacks. Transcultural nursing sensitive to cultural diversity is needed to improve health literacy, medication adherence, and reduce cardiovascular inequalities across populations.